A quantitative in silico model for predicting skin sensitization using a nearest neighbours approach within expert‐derived structure–activity alert spaces. Issue 8 (28th February 2017) - Canipa, Steven J.; Chilton, Martyn L.; Hemingway, Rachel; Macmillan, Donna S.; Myden, Alun; Plante, Jeffrey P.; Tennant, Rachael E.; Vessey, Jonathan D.; Steger‐Hartmann, Thomas; Gould, Janet; Hillegass, Jedd; Etter, Sylvain; et al.
Abstract: Dermal contact with chemicals may lead to an inflammatory reaction known as allergic contact dermatitis. Consequently, it is important to assess new and existing chemicals for their skin sensitizing potential and to mitigate exposure accordingly. There is an urgent need to develop quantitative non‐animal methods to better predict the potency of potential sensitizers, driven largely by European Union (EU) Regulation 1223/2009, which forbids the use of animal tests for cosmetic ingredients sold in the EU. A Nearest Neighbours in silico model was developed using an in‐house dataset of 1096 murine local lymph node (LLNA) studies. The EC3 value (the effective concentration of the test substance producing a threefold increase in the stimulation index compared to controls) of a given chemical was predicted using the weighted average of EC3 values of up to 10 most similar compounds within the same mechanistic space (as defined by activating the same Derek skin sensitization alert). The model was validated using previously unseen internal ( n  = 45) and external ( n  = 103) data and accuracy of predictions assessed using a threefold error, fivefold error, European Centre for Ecotoxicology and Toxicology of Chemicals (ECETOC) and Globally Harmonized System of Classification and Labelling of Chemicals (GHS) classifications. In particular, the model predicts the GHS skin sensitization category of compounds well, predicting 64% of chemicals in an external test set within the correct category. Of the remaining chemicals in the previously unseen dataset, 25% were over‐predicted (GHS 1A predicted: GHS 1B experimentally) and 11% were under‐predicted (GHS 1B predicted: GHS 1A experimentally). Copyright © 2017 John Wiley & Sons, Ltd. Abstract : A Nearest Neighbours in silico model was developed using an in‐house dataset of 1096 murine local lymph node studies. The EC3 value of a given chemical was predicted using the weighted average of EC3 values of up to 10 most similar compounds within the same mechanistic space (as defined by activating the same Derek skin sensitization alert). The model was validated using previously unseen internal ( n  = 45) and external ( n  = 103) data with good EC3 predictivity.